Equine viral encephalitis: prevalence, impact, and management strategies - Barba M (Dove Medical Press, 2019)
Marta Barba,1 Emma L Fairbanks,2 Janet M Daly21Veterinary Faculty, Universidad Cardenal Herrera-CEU, CEU Universities, Valencia, Spain; 2School of Veterinary Medicine and Science, University of Nottingham, Sutton Bonington, Leicestershire, UKAbstract: Members of several different virus families cause equine viral encephalitis, the majority of which are arthropod-borne viruses (arboviruses) with zoonotic potential. The clinical signs caused are rarely pathognomonic; therefore, a clinical diagnosis is usually presumptive according to the geographical region. However, recent decades have seen expansion of the geographical range and emergence in new regions of numerous viral diseases. In this context, this review presents an overview of the prevalence and distribution of the main viral causes of equine encephalitis and discusses their impact and potential approaches to limit their spread.Keywords: arbovirus, vector, vaccination, mathematical modeling